Enhanced IGFL1 translation in response to IL-1β is controlled by distinct 3’UTR elements - Giulia Cardamone; Melanie Flohr; Rebecca Raue; Irina Bode; Sofie P. Meyer; Sven Hauns; Rolf Backofen; Tobias Schmid (PLoS ONE, 2026)
Translation is a crucial regulatory mechanism involved in several diseases, including cancer, where pro-inflammatory conditions within the microenvironment have been shown to modulate the translation of specific mRNAs. In the present study, we focused on the regulation of insulin growth factor-like family member 1 ( IGFL1 ) in MCF7 breast cancer cells in response to pro-inflammatory IL-1β and observed an induction of both transcription and translation. We characterized the 3’ untranslated region as regulatory hub for the post-transcriptional regulation and identified a distinct G-rich region to confer the IL-1β-dependent translational increase. Our study therefore provides new insights into the translation regulation of IGFL1 in the context of an inflammatory tumor microenvironment.